STUDENTS' MASTERY OF READING SKILLS AND ITS CORRELATION WITH THEIR READING COMPREHENSION ABILITY :A study at the second year students of an SLTP in Lembang - Toba, Rostanti (2009)
This present study focuses on the students' mastery of reading skills and its correlation with their reading comprehension ability. The study intends to find out the answers to the following research problems: (1) What is students' mastery of reading skills? and (2) Is there any correlation between students' mastery of reading skills and their reading comprehension ability of the second year students of an SLTP in Lembang?. Derived from the problems mentioned above, the objectives of the study are: (1) To find out what students' mastery of reading skills is, and (2) To find out the correlation between the students' mastery of reading skills and their comprehension ability of the second year students of an SLTP in Lembang. To lead the researcher in collecting the data, a hypothesis was formulated for the study: there is a positive correlation between the students' mastery of reading skills and their reading comprehension ability. This study used a descriptive analysis method by using an ex post facto design. The target population of the study was the second year students of an SLTP in Lembang. A cluster random sampling procedure was employed by listing all the second year students of about 469 students. Then they were grouped into high achievement students and low achievement students. 20% of the whole or both groups were taken as the sample of the study (92 students). Two kinds of instruments were employed for this study: students' problems in reading (questionnaire) which was developed into Likert scale model, and reading test. Descriptive statistic of Pearson Product Moment Coefficient Correlation was used to answer the research problems by using SPSS (Statistical Package for Social Science). The data obtained from the study revealed that the value (r) of the correlation between students' mastery of reading skills and their reading comprehension ability at the level of significant .01 was -.765. It indicates that both variables are significantly correlated so that the hypothesis of the study: there is a very high significant correlation between students' mastery of reading skills and their reading comprehension ability of the second year students of an SLTP in Lembang was accepted. As students still have many problems in reading comprehension, it is suggested that for English teachers of Junior High School, it is better to help the students to overcome their problems in reading by applying and creating innovation of better and effective techniques or methods of teaching reading in the process of teaching and learning in order to increase their ability in reading comprehension. For further researches, the students' problems in reading need to be found out in different levels of students i.e. elementary school, senior high school, and college students. It is also advised for the students to get more practice in order to increase their ability in comprehending the text